Evaluasi Peraturan Daerah No. 10 Tahun 2012 Tentang Penyelenggaraan Jalan Umum Dan Jalan Khusus Untuk Kegiatan Pengangkutan Batu Barat Dan Kelapa Sawit Di Kecamatan Tenggarong Seberang Kabupaten Kutai Kartanegara - Adythia Permana Sinaga; Anwar Alaydrus; Iman Surya (Jurnal Ilmu Pemerintahan, 2023)
This study aims to determine the obstacles faced by the Government and the police in enforcing criminal law against people who violate the function of the road according to Regional Regulation No. 10 of 2012 dam to find out the efficiency of the Government in implementing Regional Regulation No. 10 of 2012. The conclusion of the study stated that the legal arrangements for the use of public roads for the transportation of mining products in the Tenggarong Seberang District area. The research method that the author uses is qualitative with an analytic descriptive approach, with data collection techniques using three ways, namely observation, interviews and documentation. In collecting data sources, the authors used a purposive sampling technique. The results of the study show that the provisions regarding road access for the transportation of coal and palm oil are still not strict because public road use permits are still being issued. And the legal consequences for the use of public roads for the transportation of mining products in the Tenggarong Seberang District area are still not very clear and firm, however, if an accident occurs which causes harm to other public road users, the transporter must be responsible for the losses incurred.